Sn-0.5Cu(-x)Al solder alloys: Microstructure-related aspects and tensile properties responses - Lima, Thiago Soares; de Gouveia, Guilherme Lisboa; Septimio, Rudimylla da Silva; da Cruz, Clarissa Barros; Silva, Bismarck Luiz; Brito, Crystopher [UNESP]; Spinelli, José Eduardo; Cheung, Noé (MDPI, 2019)
In this study, experiments were conducted to analyze the effect of 0.05 and 0.1 wt.% Al additions during the unsteady-state growth of the Sn-0.5wt.%Cu solder alloy. Various as-solidified specimens of each alloy were selected so that tensile tests could also be performed. Microstructural aspects such as the dimensions of primary, λ 1 , and secondary, λ 2 , dendritic arrays, and intermetallic compounds (IMCs) morphologies were comparatively assessed for the three tested compositions, that is, Sn-0.5wt.%Cu, Sn-0.5wt.%Cu-0.05wt.%Al, and Sn-0.5wt.%Cu-0.1wt.%Al alloys. Al addition affected neither the primary dendritic spacing nor the types of morphologies identified for the Cu 6 Sn 5 IMC, which was found to be either globular or fibrous regardless of the alloy considered. Secondary dendrite arm spacing was found to be enlarged and the eutectic fraction was reduced with an increase in the Al-content. Tensile properties remained unaffected with the addition of Al, except for the improvement in ductility of up to 40% when compared to the Sn-0.5wt.%Cu alloy without Al trace. A smaller λ 2 in size was demonstrated to be the prime microstructure parameter associated with the beneficial effect on the strength of the Sn-0.5wt.%Cu(-x)Al alloys.
Keywords: Microstructure; Sn-Cu-Al alloys; Solidification; Tensile strength